Change in psychiatric symptomatology after benfotiamine treatment in males is related to lifetime alcoholism severity. (1st July 2015) - Manzardo, Ann M.; Pendleton, Tiffany; Poje, Albert; Penick, Elizabeth C.; Butler, Merlin G.
Highlights: The high potency thiamine analogue, benfotiamine (BF), was used in men with alcoholism. Lifetime severity of alcoholism impacted psychiatric symptoms and response to BF. Depression and anxiety were reduced in the high lifetime alcoholism severity group. Benfotiamine may facilitate alcohol rehabilitation for severely affected men. Abstract: Background: Severe alcoholism can be associated with significant nutritional and vitamin deficiency, especially vitamin B1 (thiamine) which is associated with neurological deficits impacting mood and cognition. Alcohol consumption was reduced among female but not male alcoholics after supplementation with the high potency thiamine analog benfotiamine (BF). We examined the relationship between lifetime alcoholism severity, psychiatric symptoms and response to BF among the alcohol dependent men from this cohort. Methods: Eighty-five adult men (mean age = 48 ± 8 years) meeting DSM-IV-TR criteria for a current alcohol use disorder who were abstinent <30 days participated in a randomized, double-blind, placebo-controlled trial of 600 mg BF vs placebo (PL) for 6 months. Psychometric testing included a derived Lifetime Alcoholism Severity Score (AS), Symptom Checklist 90R (SCL-90R), and the Barratt Impulsivity Scale (BIS) at baseline and at 6 months. Results: Baseline SCL-90-R scale scores for men with high alcoholism severity (AS ≥ 24; N  = 46 HAS) were significantly greater than for men with low alcoholism severity (AS < 24; N  = 39 LAS), but BIS scores did not differ. MANOVA modeling at follow-up (N=50 completed subjects) identified a significant treatment effect ( F  = 2.5, df = 10, p  < 0.03) and treatment × alcoholism severity level interaction ( F  = 2.5, dfnum  = 10, dfden  = 30, p  < 0.03) indicating reduced SCL-90-R scores among BF treated, HAS males. Above normal plasma thiamine levels at follow-up predicted reduced depression scores in a BF-treated subset (F = 3.2, p < 0.09, N = 26). Conclusion: BF appears to reduce psychiatric distress and may facilitate recovery in severely affected males with a lifetime alcohol use disorder and should be considered for adjuvant therapy in alcohol rehabilitation. Trial Registration : #NCT00680121 High Dose Vitamin B1 to Reduce Abusive Alcohol Use.